Identification of a new natural gastric lipase inhibitor from star anise. Issue 1 (11th January 2019) - Kamoun, Jannet; Rahier, Renaud; Sellami, Mohamed; Koubaa, Imed; Mansuelle, Pascal; Lebrun, Régine; Berlioz-Barbier, Alexandra; Fiore, Michele; Alvarez, Karine; Abousalham, Abdelkarim; Carrière, Frédéric; Aloulou, Ahmed
Abstract : The flavonoid myricitrin-5-methyl ether is a potential drug candidate as a gastric lipase inhibitor for the treatment of obesity. Abstract : The identification and isolation of bioactive compounds are of great interest in the drug delivery field, despite being a difficult task. We describe here an innovative strategy for the identification of a new gastric lipase inhibitor from star anise for the treatment of obesity. After plant screening assays for gastric lipase inhibition, star anise was selected and investigated by bioactivity guided fractionation. MALDI-TOF mass spectrometry and peptide mass fingerprinting allowed the detection of an inhibitor covalently bound to the catalytic serine of gastric lipase. A mass-directed screening approach using UPLC-HRMS and accurate mass determination searching identified the flavonoid myricitrin-5-methyl ether (M5ME) as a lipase inhibitor. The inhibitory activity was rationalized based on molecular docking, showing that M5ME is susceptible to nucleophilic attack by gastric lipase. Overall, our data suggest that M5ME may be considered as a potential candidate for future application as a gastric lipase inhibitor for the treatment of obesity.